Poetry of discovery : the Spanish generation of 1956-1971 - Debicki, Andrew Peter (University Press of Kentucky, 1982)
A leading critic of contemporary Spanish poetry examines here the work of ten important poets who came to maturity in the immediate post-Civil War period and whose major works appeared between 1956 and 1971: Francisco Brines; Eladio Cabañero; Angel Crespo; Gloria Fuertes; Jaime Gil de Biedma; Angel González; Manuel Mantero; Claudio Rodríguez; Carlos Sahagún; and José Angel Valente. Although each of these poets has developed an individual style, their work has certain common characteristics: use of the everyday language and images of contemporary Spain, development of language codes and intertex.